2021
DOI: 10.3390/ijms22137126
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Infusion in Critically Ill COVID-19 Patients: Hemodilution and Anticoagulation

Abstract: Hypercoagulation is one of the major risk factors for ICU treatment, mechanical ventilation, and death in critically ill patients infected with SARS-CoV-2. At the same time, hypoalbuminemia is one risk factor in such patients, independent of age and comorbidities. Especially in patients with severe SARS-CoV-2-infection, albumin infusion may be essential to improve hemodynamics and to reduce the plasma level of the main marker of thromboembolism, namely, the D-dimer plasma level, as suggested by a recent report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 119 publications
(168 reference statements)
0
18
0
Order By: Relevance
“…Infusions of human albumin solution can reduce the more severe or life-threatening events that take place in COVID-19 patients [ 38 , 114 ]. However, there is no consensus as to whether simply administering albumin to patients with hypoalbuminemia reduces their morbidity and mortality [ 48 , 115 , 116 , 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…Infusions of human albumin solution can reduce the more severe or life-threatening events that take place in COVID-19 patients [ 38 , 114 ]. However, there is no consensus as to whether simply administering albumin to patients with hypoalbuminemia reduces their morbidity and mortality [ 48 , 115 , 116 , 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature indicates that hypoalbuminemia is associated with increased arterial and venous thrombosis risk in different clinical situations (16,17). Besides, a recent study has demonstrated that albumin infusion can be used to improve hemodynamics and decrease D-dimer plasma level, which is the main marker of thromboembolism, in critically ill COVID-19 patients (18).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, low albumin levels might be associated with thrombotic events in acutely ill patients, reflecting proinflammatory or hypercoagulable states [33]. In COVID-19 patients, as well as in other critical settings, low serum albumin is associated with poor outcomes [34][35][36], and albumin infusion has been suggested to be an effective treatment to improve prognosis in COVID-19 [37,38].…”
Section: Discussionmentioning
confidence: 99%